Termografia por infravermelho na gestação : mapeamento da temperatura cutânea por trimestre - Eduardo, Graziela Nogueira (2024)
INTRODUCTION: During the entire gestational period, physiological changes are observed in the maternal body systems. Although the literature indicates a tendency for body temperature to increase during this period, little is known about the skin thermal profile in each trimester. Infrared thermography is a way of monitoring skin temperature, which is safe, non-invasive, painless and has no contraindications. Therefore, it is considered an auxiliary instrument in monitoring physiological changes during pregnancy. OBJECTIVE: To understand the thermal profile of pregnant women during the first, second and third trimester of pregnancy. METHODOLOGY: This is a cross-sectional observational study carried out at the Thermography Laboratory (LabTerm) of the Federal University of Paraíba. Thermal imaging (thermography), anthropometry (stadiometer and scale), abdominal, breast and hip circumference, uterine height (flexible measuring tape) and abdominal diastasis (caliper) were evaluated in 74 normal-risk pregnant women, aged between 18 and 40 years, which will be divided into three groups according to gestational age: first, second and third trimester; in addition to 26 non-pregnant women as a comparator group. The processing and analysis of thermograms will be carried out using Teledyne Flir software. The ROIs were demarcated using polygons and analyzed according to the standard formula proposed by Nadel. The main outcome was the average skin temperature and main ROIs in pregnant women in the anterior and posterior view and the secondary outcome was the comparisons of abdominal, breast, hip, diastasis and uterine height circumferences. The analysis of statistical data will be carried out using SPSS 21.0 software. RESULTS: It was observed that the average skin temperature of pregnant women in the first trimester is higher than the average skin temperature of pregnant women in the third trimester (P<0.05); the abdominal temperature of pregnant women in the first trimester tends to be higher compared to pregnant women in the second and third trimesters (P<0.05); and the breast skin temperature of pregnant women is higher compared to non-pregnant women (P<0.05). Furthermore, there is a tendency for negative correlations between the average skin temperature and the temperature of the abdominal regions and the diastasis region with measures of fetal development. CONCLUSION: In general, it is observed that there are differences in skin temperatures in regions such as the breast between pregnant and non-pregnant women, as well as a tendency towards higher abdominal temperatures in pregnant women in the first trimester compared to those in the third trimester.